1980
DOI: 10.1099/00221287-121-1-117
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inhibitors on the Oxygen Kinetics of Terminal Oxidases of Tetrahymena pyriformis ST

Abstract: Respiration of early-exponential phase cultures of the ciliate protozoon Tetrahymena pyriformis is inhibited in two stages with increasing concentrations of cyanide. Up to 40 to 50 % inhibition occurs at low concentrations (< 15 PM). Maximal inhibition was obtained with 300pwcyanide; at this concentration 20 % of the respiration was still unaffected.Competitive inhibition of respiration by CO occurs (Ki = 4-25 p~) ; azide inhibition of oxygen consumption is uncompetitive (K, = 4 to 9 mM). A salicylhydroxamic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…The results with respect to general levels of respiration and inhibitor sensitivity for exponentially growing and stationary phase cells are in good agreement with previously published data (Ruben & Hooper, 1978;Lloyd et al, 1980;Skriver & Nilsson, 1978).…”
Section: Respiration In Tetrahyrnena and Sensitivity To Inhibitorssupporting
confidence: 92%
See 2 more Smart Citations
“…The results with respect to general levels of respiration and inhibitor sensitivity for exponentially growing and stationary phase cells are in good agreement with previously published data (Ruben & Hooper, 1978;Lloyd et al, 1980;Skriver & Nilsson, 1978).…”
Section: Respiration In Tetrahyrnena and Sensitivity To Inhibitorssupporting
confidence: 92%
“…At higher concentrations, the degree of inhibition attainable (approximately 50 % at 4 to 5 mM) suggests a non-specific effect presumably due to the chelating properties of the inhibitor. Lloyd et al (1980) found no effect of SHAM at 1 mM in whole cells in the absence of CN-; however, their cultures were at high density (4 x lo5 cells rnl-l, concentrated to 2 x lo6 cells ml-l for measurement) and therefore appear to be more typical of the stationary phase cells used here. Data on the absolute level of O2 consumption per cell were not presented by these authors so that the physiological growth state can not be assessed.…”
Section: Amount and Utilization Of The Alternative Oxidasementioning
confidence: 92%
See 1 more Smart Citation
“…min-I. Gas entry and exit ports were via the lid (Degn et al, 1980). The vessel was jacketed and supplied with water from a thermostatically controlled water heater.…”
Section: L L O Y D a N D O T H E R Smentioning
confidence: 99%
“…Maximal inhibition of respiration, thcrefore, could only be obtained in the presence of the classical inhibitors plus salicylhydroxamic acid (Lloyd et al, 1979(Lloyd et al, , 1980Mendis and Evans, 1984;Paget et al, 1987b;Zaba, 1983). The alternative pathway of A. marina seeins to differ from that of most other species since it is not completely insensitive to cyanide.…”
Section: Discussionmentioning
confidence: 99%